2014
DOI: 10.1111/anae.12798
|View full text |Cite
|
Sign up to set email alerts
|

A novel device for target controlled administration and reflection of desflurane – the Mirus

Abstract: The Anaconda™ system is used to deliver inhalational sedation in the intensive care unit in mainland Europe. The new Mirus™ system also uses a reflector like the Anaconda; however, it also identifies end-tidal concentrations from the gas flow, injects anaesthetics during early inspiration, controls anaesthetic concentrations automatically, and can be used with desflurane, which is not possible using the Anaconda. We tested the Mirus with desflurane in the laboratory. Compared with an external gas monitor, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 18 publications
0
30
0
1
Order By: Relevance
“…In our previous bench study, we found a high accuracy and precision of the end-tidal concentrations displayed by the Mirus™ (Bomberg et al 2014 ). However, there was a swing of 20 % around the target concentration with a periodicity of 2.6 min which may be criticized.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In our previous bench study, we found a high accuracy and precision of the end-tidal concentrations displayed by the Mirus™ (Bomberg et al 2014 ). However, there was a swing of 20 % around the target concentration with a periodicity of 2.6 min which may be criticized.…”
Section: Discussionmentioning
confidence: 71%
“…In our previous bench study, mean inspiratory concentrations during desflurane injections were only 134 % (SD 12 %) of the preceding end-tidal concentration (Bomberg et al 2014 ). This is unlikely to elicit sympathetic activation as described in the literature (Ebert et al 1998 ; Weiskopf et al 1994 ).…”
Section: Discussionmentioning
confidence: 82%
“…Another potential risk factor is the use of inhalational sedation devices postoperatively in the intensive care unit (ICU) for a range of different conditions [ 25 28 ]. Patients susceptible to MH also resident in the ICU may be at risk from such exposure, although administration of sevoflurane via the AnaConDa® device was found to be safe for healthcare workers with the caveat that a gas extraction system should be used in conjunction with such devices to reduce occupational exposure [ 29 ].…”
Section: Reviewmentioning
confidence: 99%
“…AnaConDa™ and MIRUS™ reflect VA and can be used with standard ICU ventilators. Both systems deliver isoflurane (ISO) and sevoflurane (SEVO), but MIRUS™ can also be used with desflurane (DES), which might be useful for short‐term sedation …”
Section: Introductionmentioning
confidence: 99%